2004
DOI: 10.1016/s0896-6273(04)00264-8
|View full text |Cite
|
Sign up to set email alerts
|

Early Amygdala Reaction to Fear Spreading in Occipital, Temporal, and Frontal Cortex

Abstract: The amygdala involvement in fear processing has been reported in behavioral, electrophysiological, and functional imaging studies. However, the literature does not provide precise data on the temporal course of facial emotional processing. Intracranial event-related potentials to facial expressions were recorded in epileptic patients implanted with depth electrodes during a presurgical evaluation. Specific potentials to fear beginning 200 ms poststimulus were observed in amygdala, both individually in two pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
183
6
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(214 citation statements)
references
References 69 publications
22
183
6
3
Order By: Relevance
“…However, there is some debate on how such rapid perception is accomplished. A fast subcortical thalamus‐amygdala route bypassing the visual cortex is thought to transmit coarse face‐related information (LeDoux, 2009; Morris et al, 1998), but its role in face perception is controversial (Krolak‐Salmon et al, 2004; Pessoa & Adolphs, 2011), including whether it is fear‐specific (Méndez‐Bértolo et al, 2016) or non‐specific to expression (Garvert, Friston, Dolan, & Garrido, 2014; McFadyen et al, 2017). On the other hand, multiple fast cortical pathways forming part of a feedforward and feedback mechanism consistute an equally plausible mechanism for rapid expression perception (Liu & Ioannides, 2010; Pessoa & Adolphs, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is some debate on how such rapid perception is accomplished. A fast subcortical thalamus‐amygdala route bypassing the visual cortex is thought to transmit coarse face‐related information (LeDoux, 2009; Morris et al, 1998), but its role in face perception is controversial (Krolak‐Salmon et al, 2004; Pessoa & Adolphs, 2011), including whether it is fear‐specific (Méndez‐Bértolo et al, 2016) or non‐specific to expression (Garvert, Friston, Dolan, & Garrido, 2014; McFadyen et al, 2017). On the other hand, multiple fast cortical pathways forming part of a feedforward and feedback mechanism consistute an equally plausible mechanism for rapid expression perception (Liu & Ioannides, 2010; Pessoa & Adolphs, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The role of the amygdala in fear perception and response was established through lesioning studies in animals and confirmed through positron emission tomography and functional magnetic resonance imaging in normal human subjects and in schizophrenic patients with deficits in fear processing (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Nous nous intéressons depuis peu à l'étude directe de la dynamique temporelle des réponses de l'amygdale à partir des signaux MEG, autrement accessible uniquement à partir d'enregistrements intra-cérébraux effectués dans un contexte préchirurgical chez des patients épileptiques [13]. Nous utilisons pour cela des méthodes de segmentation des structures du lobe temporal médian à partir des images IRM anatomiques individuelles [7].…”
Section: Une Détection Précoce ?unclassified